Mass Transfer Modelling for Compact Hybrid Membrane-Amine System in Removal of C02 from Natural Gas - Nguyen Thi, Quynh Nga (Universiti Teknologi Petronas, 2005)
The removal of CO2 from natural gas down to the pipeline quality is an important step before the natural gas can be sold to the end users. Typical natural gas treatment's specification requires that the composition of CO2 in the treated gas cannot be more than 2 mole%. Normally amine scrubbing process is extensively used to treat natural gas with low content of CO2. However, this is not efficient in dealing with natural gas with high CO2 content. Therefore, there is a proposal of using hybrid system in sequencing of membrane for bulk CO2 removal followed by amine solution for absorption process. However, there are some disadvantages for the hybrid system such as not applicable in offshore. All the disadvantages of the hybrid system will be overcome if the compact hybrid membrane-absorption column is brought into operation. This system uses the concept in which amine absorption is integrated together with the membrane permeation. The feedgas will flow along the membrane and permeate through the membrane and then will be absorbed into the amine solution. The main objective of this work is to develop a mathematical model for the removal of CO2 from natural gas in compact hybrid membrane amine system. The model has analyzed the permeability of CO2 and methane across membrane followed by absorption of CO2 in amine solution. The effect of various parameters, which consist of concentration of CO2 in feed gas, operating pressure of feed gas, flow rate of amine solution and membrane pore size, towards the permeability and separation factor of the compact hybrid membrane-amine system has been analyzed systematically. The model is developed using MATHCAD version 2000i and Microsoft Excel to represent the mass transfer of CO2 in the compact hybrid membrane-amine system. The performance of membrane separation is determined by the permeability of each component through the membrane and selectivity of the membrane for each component in the mixture. Based on the mathematical model developed, it was found that the permeability of CO2 and methane was independent of the concentration of each component in the feed gas. However, the permeability of CO2 and methane was a strong function of operating pressure at the feed gas and membrane pore size due to the effect of surface diffusion at small pore sizes, but this effect was lost at bigger pore sizes. For amine absorption, the mathematical model showed that the separation factor for removal of C02 from natural gas using compact hybrid membrane-amine system was strongly dependent on concentration of CO2 in the natural gas as well as flow rate of amine solution due to its effect on the rate of absorption. However, operating pressure of feed gas does not show any effect on the separation factor of CO2 removal. The model for compact hybrid membrane-amine absorption system is successfully developed and various operating parameters have been studied and discussed in the later section of this report.